NMR-Metabolomics Study on Falcons Affected by Aspergillosis - Pappalardo, Lucia; A. Hoijemberg, Pablo; Pelczer, Istvan; A. Bailey, Thomas (Current Metabolomics, 2014)
Respiratory diseases are a common cause of morbidity and mortality in raptors. Among these diseases, aspergillosis is one of the most important causes of mortality of falcons in the Middle East. Falcon blood (plasma) has been investigated for the first time by 1H-NMR spectroscopy and multivariate statistics in order to identify and comparatively characterize the metabolic profile of aspergillosis. Clear differences exist between the profiles of healthy and diseased subjects and lead to clean clustering in statistics. Analysis of the orthogonal projection to latent structure discriminant analysis (O-PLS-DA) coefficient plots and statistical total correlation spectroscopy (STOCSY) traces helps to identify significant components that define the separation. We have observed that 3-hydroxybutyrate is greatly increased in the diseased cohort, among a variety of other metabolic differences. Also, there is a distinctively different behavior of the very low density (VLDL) and low density lipids/lipoproteins (LDL); the heavier lipid subfractions are significantly diminished in the sick subjects. These findings serve as the first step towards developing a possible test for early diagnosis and may provide a better understanding of the underlying biochemistry of this disease.
Keywords: aspergillosis